ANALISIS DIPLOMASI INDONESIA – MALAYSIA DALAM MASALAH PERBATASAN - Achdijat Sulaeman (Universitas Nasional, 2018)
AbstractThe main function of diplomacy is to protect and promote national identity in this article will discuss the analysis of Indonesia and Malaysia diplomacy in border disputes, This will be examined by looking at the international relations which is then reviewed also the advantages and disadvantages seen in terms of policies and efforts made by the government for domestic and foreign purposes. Therefore, in this section the various studies of International Relations policy as well as activities of Indonesian society and Malaysia are the nation of one Malay family and the majority of the population are Muslim. Always between these two countries stumble stones like some cases of migrant workers, the loss of the two islands Sipadan Ligitan, the case on the Ambalat border, the Indonesian lndonesian tracking in Malaysia, the claiming of the Reog culture, the Batik, the Rasa Sayange song and a series of problems will become a common thread when dith retreats into the eyeglasses of the past. Key Words : Diplomacy,Conflict, Negotiation, Mediation, Conciliation